A fiber battery based on a braided electrode structure and a method of manufacturing the same
Patent Information
- Application Number
- CN202611287400.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]针对现有技术中纤维电池集流体结构单一、导电路径缺乏冗余、正负极相对位置不稳定以及凝胶电解质与纤维电极结构空间匹配性不足等问题,本发明提供了一种基于编织电极结构的纤维电池的制备方法,通过多根金属细丝编织形成具有三维连通导电网络的正极集流体,并结合正负极的间隔设置以及水系高分子凝胶电解质的管内原位聚合,实现纤维电池在结构完整性、柔性、电化学稳定性以及复杂机械变形条件下的工作可靠性之间的协同提升
[0027]1、本发明通过设置多根金属细丝编织形成的编织金属集流体,使纤维电池的正极集流结构由传统的一维导电形式升级为具有三维连通路径和导电冗余的柔性网络骨架,有效分散了电极截面上的电流集中分布,降低了局部电流密度峰值,从而提升了纤维电池在弯折、扭转或编织等复杂机械变形条件下的导电稳定性和电化学一致性。编织结构内部连续分布的编织间隙为正极活性材料层提供了稳定的物理约束和机械锚定条件,有利于抑制活性层在服役过程中发生脱落或开裂,增强了电极结构完整性并延长了器件的循环使用寿命。
Smart Images

Figure CN123018174A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible energy storage device technology, specifically to a fiber battery based on a braided electrode structure and its preparation method. Background Technology
[0002] With the rapid development of wearable electronic devices, flexible sensing systems, and smart textiles, wearable energy storage devices that can highly integrate energy storage functions with fiber morphology have gradually become a technological focus of common interest in industry and academia. Fiber batteries, as a type of electrochemical energy storage device with a slender shape, good flexibility, and the ability to be directly integrated into fabric structures through weaving, sewing, or knitting processes, are considered one of the key technological approaches to realizing distributed energy supply and fabric-level system integration.
[0003] Existing fiber batteries typically use single metal filaments, carbon fibers, or conductive polymer fibers as electrodes or current collectors. While these structures can achieve basic electrochemical functions in the early stages of device fabrication, they gradually reveal various structural stability and electrochemical reliability defects during actual service, especially under complex mechanical deformation conditions such as repeated bending, twisting, and weaving. Specifically, single metal filaments or solid current collectors lack structural redundancy in the radial direction, resulting in a limited number of effective conductive paths. The current is highly concentrated across the electrode cross-section, easily forming current density peaks in localized areas, which in turn induces intensified polarization, reduced utilization of active materials, and accelerated electrochemical corrosion of the current collector itself. Simultaneously, the positive electrode active material is usually loaded onto the surface of the single filament current collector in the form of a coating. Due to the large curvature of the single filament surface and the lack of mechanical constraint on the active layer, interfacial debonding, microcrack initiation, and propagation easily occur between the active material layer and the current collector during repeated bending or twisting, ultimately leading to electrical contact degradation and rapid decay of cycle capacity.
[0004] Regarding the spatial arrangement of the positive and negative electrodes, existing fiber batteries mostly employ simple parallel or coaxial arrangements. With parallel structures, the relative positions of the positive and negative electrodes are prone to fluctuations under external forces, leading to uneven local spacing and even the risk of short circuits due to direct contact between the electrodes. While coaxial structures shorten the ion transport path to some extent, their radial ion diffusion process heavily relies on the continuity and uniformity of the gel or separator. Once local structural damage occurs during service, the ion transport channel is interrupted, making it difficult to maintain the device's electrochemical operating state.
[0005] Furthermore, in terms of electrolyte systems, aqueous polymeric gel electrolytes are widely used in fiber batteries due to their inherent safety, flexibility, and good ion conductivity. However, in the absence of clear structural constraints, conventional gel electrolytes often only serve a simple filling and isolation function. Their internal ion transport paths rely on randomly distributed swollen networks, making it difficult to form stable and continuous ion migration channels along the fiber length. When the device is in a bent or braided state, the local compression or stretching of the gel network further exacerbates the non-uniformity of ion transport, leading to increased polarization at the electrode interface and deterioration of electrochemical performance.
[0006] In summary, the performance bottleneck of existing fiber batteries does not stem solely from the active materials or electrolyte system themselves, but is fundamentally limited by the single current collector structure, insufficient dimensionality of the electrode conductive paths, and the lack of spatial synergy between the electrodes and the electrolyte. Therefore, there is an urgent need for a novel fiber battery structure and its fabrication method that can maintain fiber-level flexibility while introducing structurally redundant conductive paths and achieving stable synergistic assembly of the electrodes and electrolyte. Summary of the Invention
[0007] To address the problems of existing fiber batteries, such as the single current collector structure, lack of redundancy in conductive paths, unstable relative positions of positive and negative electrodes, and insufficient spatial matching between the gel electrolyte and the fiber electrode structure, this invention provides a method for preparing a fiber battery based on a braided electrode structure. By weaving multiple metal filaments to form a positive electrode current collector with a three-dimensional interconnected conductive network, and combining the spacing of the positive and negative electrodes with in-situ polymerization of an aqueous polymer gel electrolyte within the tube, a synergistic improvement is achieved in the fiber battery's structural integrity, flexibility, electrochemical stability, and operational reliability under complex mechanical deformation conditions.
[0008] The technical solution adopted by this invention to solve its technical problem is:
[0009] A fiber battery based on a braided electrode structure includes a braided positive electrode, a fiber negative electrode, a flexible encapsulation tube, and an aqueous polymer gel electrolyte filled within the flexible encapsulation tube.
[0010] The braided positive electrode comprises a continuously extending braided metal current collector along its length and a layer of positive electrode active material loaded on the surface of the braided metal current collector. The braided metal current collector is formed by the interweaving of multiple metal filaments, transforming the traditional one-dimensional filamentary conductive form into a flexible current collector framework with three-dimensional path connectivity. Through the interweaving of the multiple metal filaments, continuously distributed braided gaps are formed within the braided metal current collector along the radial and axial directions. These gaps not only provide physical anchoring space and mechanical constraints for the loading of the positive electrode active material but also reserve a structured channel foundation for subsequent gel electrolyte permeation and ion transport. During bending, twisting, or braiding, relative slippage and misalignment can occur between the multiple metal filaments. The elastic deformation of the braided structure absorbs external mechanical stress. Even if a single metal filament experiences local defects or breakage, the remaining filaments can still maintain a continuous conductive path through the interweaving nodes, effectively avoiding overall conductivity interruption due to single-path failure. This significantly improves the structural integrity and conductive stability of the fiber battery under complex deformation conditions.
[0011] The positive electrode active material layer includes manganese dioxide, which is loaded on the outer surface of the braided metal current collector and partially penetrates into the braiding gap. The three-dimensional curved surface support of the braided structure increases the effective contact area between the active material and the current collector and disperses the interfacial stress borne by the active layer during deformation, thereby inhibiting the cracking and peeling of the active material layer.
[0012] The fiber negative electrode is a continuous zinc wire arranged along its length. The zinc wire has a diameter of 0.1-0.5 mm and serves as the main negative electrode active element and negative electrode current collector in the fiber battery, providing a stable zinc deposition and stripping interface during charging and discharging. The continuous extension of the zinc wire along the fiber length allows for efficient axial electron transport, and its flexible metallic properties endow it with good conformal bending ability.
[0013] Both the braided positive electrode and the fiber negative electrode are arranged along their length and are disposed within the flexible encapsulation tube in a straight parallel arrangement or in a mutually spirally wound manner, thus spacing the braided positive electrode and the fiber negative electrode apart. This arrangement effectively constrains the relative positions of the positive and negative electrodes within the limited cross-sectional space of the flexible encapsulation tube, which helps maintain the uniformity of the electric field distribution between the positive and negative electrodes and significantly reduces the risk of local contact caused by relative displacement of the electrodes during bending, twisting, or braiding. When the mutually spirally wound manner is adopted, the spiral structure between the positive and negative electrodes can further absorb external mechanical strain through the elastic change of the pitch. When the fiber is stretched or bent, the fine adjustment of the pitch can effectively release internal stress, thereby improving the overall flexibility while maintaining a stable spacing between the positive and negative electrodes.
[0014] The flexible encapsulation tube provides external mechanical protection, chemical isolation, and electrolyte encapsulation for the fiber battery. Its flexible tube wall allows the fiber battery to undergo macroscopic bending and torsion while maintaining the stability of its internal structure.
[0015] The aqueous polymeric gel electrolyte fills the space between and around the braided positive electrode and the fiber negative electrode, and is formed by in-situ polymerization of a gel electrolyte precursor system injected into the flexible encapsulation tube. The positive electrode active material layer includes manganese dioxide, and the gel electrolyte precursor system includes acrylamide, N-vinylpyrrolidone, zinc salt, N,N′-methylenebisacrylamide, and lithium phenyl-2,4,6-trimethylbenzoylphosphonate, with the zinc salt having a concentration of 4-5 mol / L in the aqueous solution. This in-situ polymerization method fully utilizes the low viscosity and fluidity of the precursor system before polymerization, allowing it to penetrate deeply into the braided gaps within the braided metal current collector and the narrow space between the positive and negative electrodes, forming a solid gel interface that is completely consistent with the electrode structure after polymerization. In this way, the aqueous polymer gel electrolyte not only achieves overall encapsulation and isolation fixation of the braided positive electrode and the fiber negative electrode, but also works synergistically with the braiding gaps to construct a continuously distributed ion migration channel along the fiber length direction. This provides a clear and low-resistance path for the stable migration of ions in the axial direction, effectively avoiding ion transport interruption and local polarization caused by insufficient gel filling or poor interface contact.
[0016] Preferably, the braided positive electrode and the fiber negative electrode are arranged parallel to each other at equal intervals along the fiber length direction, with an axial spacing of 0.5-5 mm between them. More preferably, the axial spacing is 1-3 mm.
[0017] Preferably, the metal filaments are stainless steel wires, and the number of stainless steel wires is 3 to 10, with a diameter of 0.05 to 0.2 mm (ideally 0.1 mm). Within this range of number and diameter, multiple stainless steel wires can provide sufficient conductive cross-section and structural strength while ensuring the overall flexibility of the fiber. Increasing the number of stainless steel wires helps to improve the conductive redundancy and current collection capacity of the braided structure, while reducing the number helps to further improve the fineness and flexibility of the fiber; the selection of the stainless steel wire diameter balances the braided density and the flexibility of the individual filaments.
[0018] Preferably, the braided metal current collector is formed by plain weave, twill weave, or a combination of plain weave and twill weave. Plain weave has the characteristics of structural stability and uniform interlacing points, which is conducive to the uniform loading of active materials; twill weave makes the metal filaments form continuous floating long segments in the axial direction, giving the braided current collector greater unidirectional flexibility and elastic recovery ability; the combination method can take into account the comprehensive requirements of structural stability and directional flexibility.
[0019] Preferably, the positive electrode active material layer further includes a conductive agent and a binder. The conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, and graphene, and the binder is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, and water-based polymer binders. The introduction of the conductive agent helps to establish an efficient electronic conduction network between the manganese dioxide active particles and between the active layer and the braided metal current collector, reducing the interfacial contact resistance. The binder is used to firmly bond the active material and the conductive agent to the surface of the braided metal current collector and impart a certain degree of mechanical flexibility and deformation resistance to the positive electrode active material layer.
[0020] Preferably, the braided positive electrode and the fiber negative electrode are arranged in a helical winding manner, with a helical winding pitch of 1~3 mm. This pitch range can achieve a good balance between the cross-sectional dimensions of the fiber battery and the target flexibility: a smaller pitch helps to increase the effective reaction area of the electrode and improve the structural compactness within a limited length, while a larger pitch helps to reduce the stiffness of the fiber battery and improve its axial tensile adaptability.
[0021] Preferably, the mass ratio of acrylamide to N-vinylpyrrolidone is 8:2, the amount of N,N′-methylenebisacrylamide added is 0.2% of the total mass of acrylamide and N-vinylpyrrolidone, and the amount of lithium phenyl-2,4,6-trimethylbenzoylphosphonate added is 0.1% of the total mass of acrylamide and N-vinylpyrrolidone. In this formulation, acrylamide, as the main monomer, provides the basic network structure of the gel backbone; the introduction of N-vinylpyrrolidone significantly improves the hydrophilicity of the gel electrolyte and its ability to solvate ions in the aqueous system, thereby enhancing the migration rate of ions in the gel network; N,N′-methylenebisacrylamide, as a crosslinking agent, forms chemical crosslinking points between polymer chains, endowing the gel with the necessary mechanical strength, shape stability, and anti-swelling ability; lithium phenyl-2,4,6-trimethylbenzoylphosphonate, as a UV-photopolymerization initiator, can efficiently generate active free radicals under 365 nm UV irradiation, rapidly initiating the copolymerization reaction of acrylamide and N-vinylpyrrolidone, achieving rapid in-situ curing of the gel precursor system within a flexible encapsulation tube. These four components work synergistically to form an aqueous polymeric gel electrolyte that combines high ionic conductivity, good mechanical flexibility, and excellent chemical stability.
[0022] Preferably, the zinc salt is selected from one or more of zinc sulfate, zinc chloride, and zinc trifluoromethanesulfonate, and the material of the flexible encapsulation tube is selected from one of polyethylene, polypropylene, polyurethane, ethylene-vinyl acetate copolymer, and polytetrafluoroethylene. The aforementioned zinc salt can provide a high concentration of zinc ions in the aqueous system, serving as the main ion source in the gel electrolyte and participating in the zinc deposition and stripping reactions at the negative electrode and the manganese dioxide reduction and oxidation reactions at the positive electrode. The high concentration of zinc salt also helps to reduce the bulk resistance of the gel electrolyte and improve the rate performance of the fiber battery.
[0023] Preferably, the flexible encapsulation tube has an inner diameter of 0.8-2.0 mm and a wall thickness of 0.1-0.8 mm.
[0024] A method for preparing the above-mentioned fiber battery based on a braided electrode structure includes the following steps: S1 Preparation step, using multiple metal filaments to weave together to form a braided metal current collector that extends continuously along the length direction; S2 Loading step, coating a positive electrode slurry including manganese dioxide onto the surface of the braided metal current collector and drying it to form a braided positive electrode; S3 Arrangement step, providing zinc wires continuously arranged along the length direction as fiber negative electrodes, arranging the braided positive electrode and the fiber negative electrode along the length direction, and placing them together in a flexible encapsulation tube in a straight parallel manner or in a spiral winding manner, so that the braided positive electrode and the fiber negative electrode are spaced apart from each other; S4 Gel formation step, injecting a gel electrolyte precursor system including acrylamide, N-vinylpyrrolidone, zinc salt, N,N′-methylenebisacrylamide and lithium phenyl-2,4,6-trimethylbenzoylphosphonate into the flexible encapsulation tube, wherein the concentration of the zinc salt in the aqueous solution is 4-5 mol / L, and at 365°C... In-situ polymerization is carried out under nm ultraviolet light irradiation to form an aqueous polymer gel electrolyte that fills the space between and around the braided positive electrode and the fiber negative electrode; in the S5 encapsulation step, the flexible encapsulation tube is sealed to obtain the fiber battery.
[0025] This method achieves continuous production of braided metal current collectors through a preparation step, stabilizes the positive electrode active material on the surface and gaps of the braided structure through a loading step, achieves precise positioning and spacing constraints of the positive and negative electrodes within the encapsulation tube through an arrangement step, achieves in-situ matching and curing of the gel electrolyte and electrode structure through a gelation step, and finally completes the sealing and molding of the device through an encapsulation step. Each step is interconnected, jointly ensuring a high degree of consistency in the structure and performance of the fiber battery.
[0026] The beneficial effects of this invention are:
[0027] 1. This invention upgrades the positive electrode current collector structure of a fiber battery from a traditional one-dimensional conductive form to a flexible network skeleton with three-dimensional connectivity and conductive redundancy by incorporating a braided metal current collector formed by multiple fine metal filaments. This effectively disperses the concentrated current distribution on the electrode cross-section, reduces local current density peaks, and thus improves the conductivity stability and electrochemical consistency of the fiber battery under complex mechanical deformation conditions such as bending, twisting, or weaving. The continuously distributed weaving gaps within the braided structure provide stable physical constraints and mechanical anchoring conditions for the positive electrode active material layer, which helps to suppress the shedding or cracking of the active layer during service, enhances the integrity of the electrode structure, and extends the cycle life of the device.
[0028] 2. By arranging the braided positive electrode and the fiber negative electrode in a straight parallel manner or in a spiral winding manner along the length direction and maintaining a stable interval, the present invention effectively constrains the relative positions of the positive and negative electrodes within a limited fiber cross-sectional space. This helps to maintain the uniformity of the electric field distribution and avoids the risk of electrical contact instability and short circuit caused by local spacing fluctuations.
[0029] 3. This invention utilizes in-situ polymerization of an aqueous polymeric gel electrolyte within a packaged tube, enabling the low-viscosity gel precursor system to fully penetrate and fill the gaps in the braid and the space between the positive and negative electrodes. After polymerization, a gel interface is formed that is tightly fitted to the electrode structure. This achieves electrode fixation and electrical isolation while simultaneously constructing ion migration channels that are continuously distributed along the fiber length, providing a stable and low-resistance migration path for ions, effectively reducing internal resistance and improving the reversibility of the electrochemical reaction.
[0030] Furthermore, this invention, through the synergistic design of acrylamide, N-vinylpyrrolidone, N,N′-methylenebisacrylamide, and lithium phenyl-2,4,6-trimethylbenzoylphosphonate, and the setting of a high ion concentration of 4-5 mol / L zinc salt, enables the aqueous polymer gel electrolyte to possess excellent ion conductivity, mechanical flexibility, and interfacial adhesion, further ensuring the electrochemical stability of the fiber battery during dynamic deformation. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the braided structure of the braided metal current collector before it forms the braided positive electrode, as provided in Example 1.
[0032] Figure 2 This is a photograph of the actual product after the braided positive electrode load positive electrode active material layer provided in Example 1;
[0033] Figure 3 This is a scanning electron microscope image of the braided positive electrode with a positive electrode active material layer provided in Example 1;
[0034] Figure 4This is a partial cross-sectional view of the axial structure of the fiber battery provided in Example 1;
[0035] Figure 5 This is a schematic diagram of the internal structure of the fiber battery provided in Example 1;
[0036] Figure 6 The 10cm long fiber battery provided in Example 1 operates at a current density of 1A g. -1 Long-cycle test diagram under certain conditions;
[0037] Figure 7 The 10 cm long fiber batteries prepared in the examples and comparative examples are at 1 A g. -1 Long-cycle test diagram under certain conditions;
[0038] Figure 8 This is a comparison chart showing the capacity retention of 10cm long fiber batteries prepared in the examples and comparative examples after 1000 bending cycles.
[0039] Figure 9 The impedance comparison test of the 10cm long fiber batteries prepared in the examples and comparative examples after 1000 bending cycles is shown.
[0040] In the diagram: 1 is the braided positive electrode, 2 is the fiber negative electrode, 3 is the flexible encapsulation tube, and 4 is the aqueous polymer gel electrolyte. Detailed Implementation
[0041] The technical solution of the present invention will be further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications and / or alterations made to the present invention will fall within the protection scope of the present invention.
[0042] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.
[0043] Unless otherwise specified, the reagents used in the following examples can be purchased from a regular biochemical reagent store.
[0044] Example 1
[0045] A method for fabricating a fiber battery based on a braided electrode structure specifically includes the following steps:
[0046] 1. Preparation steps: Select 5 stainless steel wires with a diameter of 0.1 mm as metal wires, and braid them using a braiding machine (e.g., ...). Figure 1As shown, multiple stainless steel wires are interwoven along their length to form a braided metal current collector that extends continuously along the axial direction and has a uniform structure. This braided metal current collector has a three-dimensional interconnected conductive path and continuously distributed braiding gaps.
[0047] 2. Loading Step: Manganese dioxide powder, conductive carbon black, and polyvinylidene fluoride binder were weighed at a mass ratio of 7:2:1. An appropriate amount of N-methylpyrrolidone was added as a solvent, and the mixture was thoroughly stirred and dispersed to form a uniform positive electrode slurry. Subsequently, the obtained positive electrode slurry was uniformly coated onto the outer surface of the braided metal current collector, allowing the slurry to partially penetrate into the braided gaps within the current collector to enhance the mechanical bond between the positive electrode active material layer and the current collector. After coating, the mixture was dried at 60°C to allow the solvent to fully evaporate, forming a continuous and robust positive electrode active material layer on the surface of the braided metal current collector, thus obtaining the braided positive electrode. A photograph of the braided positive electrode after loading the positive electrode active material layer is shown below. Figure 2 The scanning electron microscope image of the braided positive electrode with loaded positive electrode active material layer is shown below. Figure 3 ,according to Figure 3 It can be seen that the surface of the braided positive electrode is completely covered by a continuous and dense α-MnO2 coating, and no obvious cracks, holes or peeling areas were observed.
[0048] 3. Arrangement Steps: Select zinc wire with a diameter of 0.3 mm as the fiber negative electrode. Arrange the braided positive electrode and zinc wire along their length and spirally wind them together with a pitch of approximately 2 mm, ensuring that the braided positive electrode and fiber negative electrode are spaced apart and do not directly contact each other. Subsequently, place the spirally wound braided positive electrode and fiber negative electrode together into a polyurethane flexible encapsulation tube with an inner diameter of 1.2 mm and a wall thickness of 0.3 mm, so that the positive and negative electrodes maintain a stable relative position within the encapsulation tube.
[0049] Step 4: Preparation of the gel electrolyte precursor system. Weigh acrylamide and N-vinylpyrrolidone to a mass ratio of 8:2. Add deionized water to the monomer mixture to prepare an aqueous solution with a total monomer mass fraction of 25%. Then, add zinc sulfate (ZnSO4) to the aqueous solution to achieve a zinc sulfate concentration of 4 mol / L. Simultaneously, add N,N′-methylenebisacrylamide as a crosslinking agent at a mass ratio of 0.2% of the total mass of acrylamide and N-vinylpyrrolidone; add lithium phenyl-2,4,6-trimethylbenzoylphosphonate as a photoinitiator at a mass ratio of 0.1% of the total mass of acrylamide and N-vinylpyrrolidone. After thorough stirring and dissolution, a clear gel electrolyte precursor system is obtained. Inject this precursor system into the flexible encapsulation tube containing the braided positive electrode and fiber negative electrode, ensuring that the precursor system fully fills the gaps between the braided positive electrode and the fiber negative electrode, as well as the braided gaps inside the braided metal current collector. Subsequently, the flexible encapsulation tube was irradiated with 365 nm ultraviolet light at an intensity of 30 mW / cm² for 15 min, initiating an in-situ free radical copolymerization reaction between acrylamide and N-vinylpyrrolidone. This resulted in the formation of a three-dimensional network structure of aqueous polymeric gel electrolyte through the crosslinking effect of N,N′-methylenebisacrylamide. During polymerization, this gel electrolyte tightly adhered to the interfaces of the braided positive electrode and the fiber negative electrode, forming a complete encapsulation and isolation fixation for both.
[0050] 5. Encapsulation Steps: After the gel electrolyte has fully polymerized, heat seal (or mechanically seal) both ends of the flexible encapsulation tube to prevent leakage of the gel electrolyte precursor system or aqueous polymer gel electrolyte, while avoiding the intrusion of external water vapor and oxygen, thereby obtaining a fiber battery based on a braided electrode structure.
[0051] like Figure 4 and Figure 5 As shown, in this fiber battery, the braided positive electrode 1 and the fiber negative electrode 2 are jointly disposed in the flexible encapsulation tube 3. The aqueous polymer gel electrolyte 4 is filled between the braided positive electrode 1 and the fiber negative electrode 2 and in the braided gap inside the braided positive electrode 1, forming a continuous ion migration channel along the fiber length direction.
[0052] Example 2
[0053] A method for preparing a fiber battery using a twill-woven positive electrode and an optimized gel electrolyte formulation, comprising the following steps:
[0054] 1. Preparation steps: Seven stainless steel wires with a diameter of 0.08 mm were selected and braided in a twill pattern using a braiding machine to obtain a more flexible braided metal current collector. The twill weave allows the stainless steel wires to form continuous floating segments in the axial direction, giving the braided current collector greater unidirectional flexibility and elastic recovery capability.
[0055] 2. Loading Step: A positive electrode slurry is prepared using manganese dioxide, carbon nanotubes, and polyvinylidene fluoride binder, with carbon nanotubes acting as a conductive agent. The positive electrode slurry is uniformly coated onto the surface of the braided metal current collector, allowing it to fully penetrate into the braided gaps. After drying, a braided positive electrode is obtained.
[0056] 3. Arrangement Steps: Select a zinc wire with a diameter of 0.2 mm as the fiber negative electrode. Wrap the braided positive electrode and the zinc wire together spirally with a pitch of approximately 1 mm, and place them together into a flexible encapsulation tube with an inner diameter of 1.0 mm. The wall thickness of the flexible encapsulation tube is 0.25 mm. The braided positive electrode and the zinc wire are spaced apart inside the encapsulation tube and do not come into direct contact.
[0057] 4. Gel-forming step: Weigh acrylamide and N-vinylpyrrolidone to a mass ratio of 8:2, and add deionized water to prepare an aqueous solution with a total monomer mass fraction of 20%. Based on 100 g of the gel electrolyte precursor system, the total mass of acrylamide and N-vinylpyrrolidone is 20 g, of which acrylamide is 16 g, N-vinylpyrrolidone is 4 g, and the remaining aqueous phase is used to dissolve the zinc salt and form the gel precursor system. Add zinc trifluoromethanesulfonate (Zn(CF3SO3)2)2 to the above aqueous solution to achieve a concentration of 4 mol / L. Add N,N′-methylenebisacrylamide as a crosslinking agent, at a concentration of 0.2% of the total mass of acrylamide and N-vinylpyrrolidone; add lithium phenyl-2,4,6-trimethylbenzoylphosphonate as a photoinitiator, at a concentration of 0.1% of the total mass of acrylamide and N-vinylpyrrolidone. The mixture was stirred thoroughly until all components were uniformly dissolved, resulting in a flowable gel electrolyte precursor system. This precursor system was injected into the aforementioned ethylene-vinyl acetate copolymer flexible encapsulation tube, ensuring it fully penetrated the gaps between the filaments inside the twill-braided positive electrode and the space between the positive and negative electrodes. Subsequently, the tube was irradiated with 365 nm ultraviolet light at an intensity of 40 mW / cm² for 10 min. Under ultraviolet irradiation, acrylamide and N-vinylpyrrolidone underwent in-situ copolymerization, forming a crosslinked network through N,N′-methylenebisacrylamide, resulting in an aqueous polymeric gel electrolyte continuously filling the space between the positive and negative electrodes.
[0058] 5. Packaging Steps: The two ends of the flexible packaging tube are sealed to obtain the fiber battery. The fiber battery obtained in this embodiment maintains stable charge and discharge behavior under multiple bending conditions.
[0059] Example 3
[0060] A method for preparing highly flexible fiber batteries suitable for fabric integration, comprising the following steps:
[0061] 1. Preparation Steps: Five stainless steel wires with a diameter of 0.1 mm were selected and a braided metal current collector with higher porosity was prepared by combining them in a braiding method. This combined braiding method combines the characteristics of plain weave and twill weave, giving the braided metal current collector both a uniform and stable interwoven structure and enhanced flexibility in a specific direction. The combined braiding structure extends continuously along the fiber axis and forms continuously distributed braiding gaps between adjacent metal wires to improve the wetting and filling capacity of subsequent positive electrode slurry and gel electrolyte.
[0062] 2. Loading Step: Manganese dioxide, graphene conductive agent, and polyvinylidene fluoride binder are mixed at a mass ratio of 7:2:1, and N-methylpyrrolidone is added as a solvent. The mixture is stirred thoroughly to form a uniform positive electrode slurry. The resulting positive electrode slurry is loaded onto the surface of the braided metal current collector, with some slurry entering the braiding gaps. After coating, the mixture is dried at 60 °C to disperse the graphene conductive agent in the active material layer and braiding gaps, resulting in a highly flexible braided positive electrode.
[0063] 3. Arrangement Steps: Select a zinc wire with a diameter of 0.15 mm as the fiber negative electrode. After spirally winding the braided positive electrode and the zinc wire together with a pitch of approximately 3 mm, place them together into a polyethylene flexible encapsulation tube with an inner diameter of 1.5 mm. The wall thickness of the polyethylene flexible encapsulation tube is 0.30 mm. The braided positive electrode and the fiber negative electrode are spaced apart, and their relative positions along the fiber length direction are maintained by the spiral winding structure.
[0064] 4. Gel Formation Step: An aqueous gel electrolyte precursor system containing zinc salt is injected into a flexible encapsulation tube. This precursor system includes acrylamide, N-vinylpyrrolidone, zinc salt, N,N′-methylenebisacrylamide, and lithium phenyl-2,4,6-trimethylbenzoylphosphonate. The concentration of zinc salt in the aqueous solution is 4 mol / L. In-situ polymerization is carried out under mild conditions with 365 nm ultraviolet light irradiation, allowing the aqueous polymeric gel electrolyte to form a complete coating on the positive and negative electrodes within the encapsulation tube and constructing continuous ion migration channels along the fiber length. Acrylamide and N-vinylpyrrolidone are weighed to a mass ratio of 8:2, and deionized water is added to prepare an aqueous solution with a total monomer mass fraction of 30%. Based on 100 g of the gel electrolyte precursor system, the total mass of acrylamide and N-vinylpyrrolidone is 30 g, of which acrylamide is 24 g and N-vinylpyrrolidone is 6 g. Zinc chloride (ZnCl2) was added to the resulting aqueous system to achieve a zinc chloride concentration of 4 mol / L. Subsequently, N,N′-methylenebisacrylamide was added as a crosslinking agent, at a concentration of 0.25% of the total mass of acrylamide and N-vinylpyrrolidone; lithium phenyl-2,4,6-trimethylbenzoylphosphonate was added as a photoinitiator, at a concentration of 0.15% of the total monomer mass. The mixture was stirred thoroughly until all components were uniformly dissolved, yielding a gel electrolyte precursor system. This gel electrolyte precursor system was injected into a flexible polyethylene encapsulation tube, filling the gaps between the braided positive electrode fibers and the space between the braided positive electrode and the zinc wire negative electrode. In-situ photopolymerization was then performed using 365 nm ultraviolet light at an intensity of 25 mW / cm² for 20 min. Under ultraviolet light irradiation, acrylamide and N-vinylpyrrolidone undergo free radical copolymerization and form a three-dimensional cross-linked network under the action of N,N′-methylenebisacrylamide, so that the aqueous polymer gel electrolyte can be integrally coated on the positive and negative electrodes in the encapsulation tube, and the electrolyte phase is continuously distributed along the fiber length direction.
[0065] 5. Packaging Steps: Seal both ends of the flexible packaging tube to obtain the fiber battery. This fiber battery can be directly woven or sewn, making it suitable for integration into fabric energy storage and wearable systems.
[0066] Comparative Example 1
[0067] A fiber battery based on a single stainless steel wire current collector is prepared using essentially the same method as in Example 1, except that in the preparation step, a single stainless steel wire with a diameter of 0.3 mm is used instead of five stainless steel wires with a diameter of 0.1 mm, and is directly used as the positive electrode current collector without braiding. In the loading step, a positive electrode slurry with the same composition as in Example 1 is coated on the surface of the single stainless steel wire, and after drying, a non-braided positive electrode structure is formed. The remaining arrangement steps, polymerization steps, and encapsulation steps are consistent with those in Example 1.
[0068] Because a single stainless steel wire has a smooth surface and a large curvature, the adhesion of the cathode slurry to its surface mainly relies on two-dimensional interfacial adhesion, lacking the physical fixation and gap constraints provided by a braided structure. During bending or twisting, the interfacial stress between the single stainless steel wire and the cathode active material layer concentrates, easily leading to cracking or detachment of the active layer. Simultaneously, a single metal wire lacks the multi-path conductive redundancy of a multi-strand braided structure; when localized interfacial damage, corrosion, or structural failure occurs, its electron transport continuity is more easily affected.
[0069] Comparative Example 2
[0070] A fiber battery employing a pre-formed gel electrolyte strip is prepared using essentially the same method as in Example 1, except that in the gelation step, instead of in-situ polymerization by injecting a gel electrolyte precursor system, the pre-formed aqueous polymeric gel electrolyte strip is directly inserted into a flexible encapsulation tube containing a braided positive electrode and a fiber negative electrode. This pre-formed gel electrolyte strip is pre-formed from a gel with the same chemical composition as that polymerized in Example 1 using a mold, but its shape is a cylindrical strip of fixed dimensions.
[0071] Because preformed gel electrolyte strips have fixed macroscopic dimensions and lower flexibility than the precursor solution before polymerization, they are difficult to completely fill the tiny braided gaps inside the braided metal current collector and the complex interface space between the positive and negative electrodes during insertion. This easily leads to the formation of unfilled areas or interface gaps inside the encapsulation tube, resulting in increased contact resistance between the gel and the electrodes and disrupting the continuity of ion migration channels.
[0072] The fiber batteries obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, including long-cycle stability tests, bending service tests, electrochemical impedance tests, and cross-sectional micromorphology observations.
[0073] Long-cycle stability testing was performed using a battery testing system with constant current charge-discharge capability. Before testing, the fiber battery was allowed to stand at 25±2 ℃ to stabilize its electrochemical state; subsequently, it was charged at 1 A·g within a voltage range of 0.8–1.8 V. -1 Constant current charge-discharge cycle (current density) Figure 7 The specific capacity was calculated based on the mass of the positive electrode active material MnO2, and the charge-discharge specific capacity for each cycle was recorded. To ensure comparability between the examples and comparative examples, all samples were tested under the same voltage range, current density, ambient temperature, and number of cycles.
[0074] The bending service test was conducted using a fixed-radius bending method. The fiber battery was repeatedly bent, with each bend from an initial straight state to 90° and then back to the initial state being recorded as one bending cycle, for a total of 1000 cycles. The discharge capacity of the fiber battery was measured before and after bending, and the capacity retention rate was calculated based on the ratio of the discharge capacity after bending to the discharge capacity before bending. Figure 8 All embodiments and comparative examples were conducted under the same bending radius, bending angle, number of bends, and testing conditions.
[0075] Electrochemical impedance spectroscopy (EIS) tests were performed using an electrochemical workstation, with the fiber cells under the same state of charge. The AC perturbation voltage was set to 5–10 mV, and the test frequency range was 0.01 Hz–100 kHz. The ohmic resistance and interfacial charge transfer impedance of the fiber cells were analyzed based on the obtained Nyquist plots, and the impedance changes before and after bending, as well as between different embodiments and comparative examples, were compared. Figure 9 ).
[0076] The cross-sectional microstructure was observed using a scanning electron microscope. After 1000 bending tests, the fiber battery was prepared into cross-sections. The cross-sectional morphology was observed while maintaining the relative positions of the positive electrode, negative electrode, gel electrolyte, and encapsulation structure. The analysis focused on the filling state of the gaps between the braided sections by the gel electrolyte, the interfacial contact between the electrode and the gel, and whether cracks, peeling, or detachment of the active material layer existed after bending.
[0077] Table 1. Performance Comparison of Examples and Comparative Examples
[0078]
[0079] Combined with Table 1 and Figure 6 The results of the long-cycle test shown indicate that:
[0080] Compared to Comparative Example 1, Example 1 exhibits significantly superior performance in terms of cycle stability and capacity retention after bending. From a microstructural perspective, Comparative Example 1 uses a single stainless steel wire as the positive electrode current collector, resulting in a typical one-dimensional conductive path and highly concentrated current across the cross-section, leading to a high local current density. During electrochemical cycling, this high local current density exacerbates electrochemical polarization on the current collector surface and the uneven utilization of the active material, thus accelerating capacity decay. More critically, under mechanical deformation conditions, the single stainless steel wire lacks structural redundancy. When localized areas experience interface damage, corrosion, or structural failure, its continuous electron transport is more easily affected, leading to increased internal resistance and decreased cycle performance.
[0081] Example 1 uses five 0.1 mm diameter stainless steel wires woven together to form a braided metal current collector. The interweaving of multiple filaments creates a conductive network with three-dimensional interconnected paths, allowing electrons to be dispersed and transported among the filaments, effectively reducing the current density load on a single filament. The interlacing nodes and gaps within the braided structure ensure that the positive electrode active material layer not only adheres to the outer surface of the current collector but is also partially embedded within the gaps, forming a mechanically interlocked structure. During bending or twisting, the braided metal current collector can absorb external stress through the relative slippage between the filaments and the elastic deformation of the braided gaps, resulting in a stress dispersion effect far superior to that of a single-filament structure. Even if individual filaments are damaged under extreme deformation, the remaining filaments can still maintain a certain continuity of electron transport, thereby improving the conductivity reliability and structural stability of the fiber battery under mechanical deformation conditions.
[0082] Compared to Comparative Example 2, Example 1 exhibits significant advantages in gel filling uniformity and interfacial ion transport. Comparative Example 2 uses pre-formed gel electrolyte strips directly inserted into the encapsulation tube. Due to the fixed macroscopic dimensions and limited flexibility of the pre-formed gel, it is difficult to adapt to the complex surface morphology and internal braiding gaps of the braided metal current collector. During insertion, interfacial gaps easily form between the gel and the braided positive and fiber negative electrodes, and these gaps are often not effectively filled. This forces ions to bypass these unfilled areas during transport, resulting in a tortuous transport path and increased resistance. Simultaneously, insufficient gel filling also means that the positive and negative electrodes lack stable dielectric support during bending, causing fluctuations in their relative positions.
[0083] Example 1 employed an in-situ polymerization process within the tube. Prior to polymerization, the gel electrolyte precursor system possessed low viscosity and high fluidity similar to aqueous solutions, enabling it to spontaneously penetrate and completely fill all the gaps in the braided metal current collector and the space between the braided positive electrode and the fiber negative electrode. Under 365 nm ultraviolet light irradiation, the photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphonate was photoexcited and generated free radicals, subsequently initiating a copolymerization reaction between acrylamide and N-vinylpyrrolidone. Simultaneously, N,N′-methylenebisacrylamide acted as a crosslinking agent, forming chemical crosslinking points between the polymer chains, thus transforming the flowable precursor system in situ into a three-dimensional crosslinked aqueous polymeric gel electrolyte. This in-situ polymerization process resulted in a relatively tight and continuous interfacial contact between the gel electrolyte and the braided positive and fiber negative electrodes, and ensured that the gel electrolyte fully filled the gaps in the braids and between the positive and negative electrodes, maintaining a continuous distribution of the electrolyte phase along the fiber length direction, thereby reducing ion transport interruptions caused by local voids and interfacial detachment.
[0084] The 8:2 mass ratio copolymer system of acrylamide and N-vinylpyrrolidone used in Examples 1-3 combines the mechanical strength of polyacrylamide with the high hydrophilicity of poly(N-vinylpyrrolidone). The introduction of N-vinylpyrrolidone significantly improves the affinity of the gel network for the aqueous system and its solvation ability for zinc ions. Combined with a high concentration of 4 mol / L zinc salt, abundant mobile ion carriers are formed inside the gel electrolyte, thereby achieving high ionic conductivity. Appropriate crosslinking of N,N′-methylenebisacrylamide prevents excessive swelling and shape collapse of the gel in an aqueous environment, maintaining stable dimensions and mechanical support within the flexible encapsulation tube. Lithium phenyl-2,4,6-trimethylbenzoylphosphonate can initiate the polymerization of acrylamide and N-vinylpyrrolidone under 365 nm UV irradiation, enabling the gel precursor system to form in situ inside the encapsulation tube. Acrylamide and N-vinylpyrrolidone copolymerize under photoinitiation conditions and form a cross-linked polymer network under the action of MBAA. The zinc salt electrolyte is retained in this network, thereby forming an aqueous gel electrolyte that has both ion transport capabilities and structural support.
[0085] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since it corresponds to the method disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to in the method section.
Claims
1. A fiber battery based on a braided electrode structure, characterized in that, The fiber battery includes a braided positive electrode, a fiber negative electrode, a flexible encapsulation tube, and an aqueous polymer gel electrolyte filled within the flexible encapsulation tube. The braided positive electrode includes a braided metal current collector that extends continuously along the length direction and a positive electrode active material layer loaded on the surface of the braided metal current collector. The braided metal current collector is formed by multiple metal filaments interwoven with each other. Both the braided positive electrode and the fiber negative electrode are arranged along the length direction and are arranged in a straight parallel manner or in a spiral winding manner within the flexible encapsulation tube, so that the braided positive electrode and the fiber negative electrode are spaced apart from each other; The aqueous polymeric gel electrolyte is filled between and around the braided positive electrode and the fiber negative electrode, and is formed by in-situ polymerization of the gel electrolyte precursor system injected into the flexible encapsulation tube.
2. The fiber battery according to claim 1, characterized in that, The fiber negative electrode is a continuous zinc wire arranged along its length, the diameter of which is 0.1-0.5 mm; the metal wire is a stainless steel wire, the number of which is 3 to 10, and the diameter of which is 0.05 to 0.2 mm.
3. The fiber battery according to claim 1, characterized in that, The positive electrode active material layer includes manganese dioxide, and the gel electrolyte precursor system includes acrylamide, N-vinylpyrrolidone, zinc salt, N,N′-methylenebisacrylamide and lithium phenyl-2,4,6-trimethylbenzoylphosphonate, wherein the concentration of zinc salt in the aqueous solution is 4-5 mol / L.
4. The fiber battery according to claim 1, characterized in that, The positive electrode active material layer further includes a conductive agent and a binder. The conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, and graphene, and the binder is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, and water-based polymer binders.
5. The fiber battery according to claim 1, characterized in that, The braided metal current collector is formed by plain weave, twill weave, or a combination of plain weave and twill weave; the braided positive electrode and the fiber negative electrode are arranged in a spiral winding manner, and the spiral winding pitch is 1 to 3 mm.
6. The fiber battery according to claim 3, characterized in that, The mass ratio of acrylamide to N-vinylpyrrolidone is 8:2, the amount of N,N′-methylenebisacrylamide added is 0.2% of the total mass of acrylamide and N-vinylpyrrolidone, and the amount of lithium phenyl-2,4,6-trimethylbenzoylphosphonate added is 0.1% of the total mass of acrylamide and N-vinylpyrrolidone.
7. The fiber battery according to claim 1, characterized in that, The zinc salt is selected from one or more of zinc sulfate, zinc chloride, and zinc trifluoromethanesulfonate, and the material of the flexible encapsulation tube is selected from one of polyethylene, polypropylene, polyurethane, ethylene-vinyl acetate copolymer, and polytetrafluoroethylene.
8. A method for preparing the fiber battery according to any one of claims 1 to 7, characterized in that... The method includes the following steps: The S1 preparation step involves weaving multiple metal filaments to form a braided metal current collector that extends continuously along its length. In the S2 loading step, a positive electrode slurry including manganese dioxide is coated onto the surface of the braided metal current collector and dried to form a braided positive electrode; In step S3, zinc wires are continuously arranged along the length direction as fiber negative electrodes. The braided positive electrode and the fiber negative electrode are both arranged along the length direction and placed together in the flexible encapsulation tube in a straight parallel manner or in a spiral winding manner, so that the braided positive electrode and the fiber negative electrode are spaced apart from each other. In step S4, a gel electrolyte precursor system comprising acrylamide, N-vinylpyrrolidone, zinc salt, N,N′-methylenebisacrylamide, and lithium phenyl-2,4,6-trimethylbenzoylphosphonate is injected into the flexible encapsulation tube. The zinc salt is present in an aqueous solution at a concentration of 4-5 mol / L. The system is then polymerized in situ under 365 nm ultraviolet light to form an aqueous polymer gel electrolyte that fills the space between and around the braided positive electrode and the fiber negative electrode. In the S5 encapsulation step, the flexible encapsulation tube is sealed to obtain the fiber battery.
9. The method according to claim 8, characterized in that, The braided metal current collector is prepared by using 3 to 10 stainless steel wires with a diameter of 0.05 to 0.2 mm in plain weave, twill weave, or a combination of both. The positive electrode slurry includes manganese dioxide, a conductive agent, and a binder.
10. The method according to claim 8, characterized in that, The mass ratio of acrylamide to N-vinylpyrrolidone is 8:2, the amount of N,N′-methylenebisacrylamide added is 0.2% of the total mass of acrylamide and N-vinylpyrrolidone, the amount of lithium phenyl-2,4,6-trimethylbenzoylphosphonate added is 0.1% of the total mass of acrylamide and N-vinylpyrrolidone, and the zinc salt is selected from one or more of zinc sulfate, zinc chloride, and zinc trifluoromethanesulfonate.